A Review of Olanzapine in the Treatment of Cancer Anorexia-Cachexia Syndrome - Ivy O. Poon; Veronica Ajewole; Ursula K. Braun (MDPI AG, 2024)
Background: Cancer anorexia-cachexia syndrome (CAS) is a multifactorial condition that is highly prevalent in advanced cancer patients and associated with significant reduction in functional performance, reduction in quality of life, and increased mortality. Currently, no medications are approved for this indication. Recently, the American Society of Clinical Oncology (ASCO) released a rapid recommendation suggesting that low-dose olanzapine once daily may be used to treat cancer cachexia. Many questions still exist on how to use olanzapine for this indication in clinical practice. The objective of this review is to identify existing knowledge on the use of olanzapine for CAS. Methods: A comprehensive search was conducted to identify the primary literature that involved olanzapine for anorexia and cachexia in cancer patients between 2000 and 2023. Results: Seven articles were identified and are discussed here, including two randomized double-blinded placebo-controlled studies, one randomized comparative study, two prospective open-label studies, one retrospective chart review, and one case report. Conclusions: Low dose olanzapine (2.5-5 mg once daily) may be useful in the treatment of CAS for increasing appetite, reducing nausea and vomiting, and promoting weight gain. Further large-scale multi-center randomized placebo-controlled studies will be needed to investigate the impact of olanzapine on weight change in CAS patients.